Perceived Need Factor Analysis on the Utilization of Elderly Health Services in Puskesmas and Posyandu - Della Trinanta Acesania Tumangger (STIKes Hang Tuah Pekanbaru, 2021)
The need factor-based to the theory of Andersen and Newman (2005) is seen from 2 aspects, which include the individual assessment aspect (perceived need factor) and the clinical aspect (evaluated need). There is still no publication of review research that discusses specific analyzes of subjective assessment of the needs of the elderly on the use of services in health facilities at Puskesmas and Posyandu. The purpose of this study was to identify the relationship between the influence of perceived need factors on the utilization of health services for the elderly at the Puskesmas and Posyandu. This study is a qualitative study with a literature review using quantitative and mixed methods analysisÂ which areÂ published from 2016 to 2021. The collection of literature using the Scopus, Science Direct, PubMed, and Google Scholar databases. The search results obtained 60 articles that matched the keywords and then the overall identification was carried out using inclusion and exclusion criteria in the content of the article so that 12 articles were reviewed. The results showed which variable of perceived need factor that most commonly found to be related to the utilization of elderly health care services at Puskesmas and Posyandu was the chronic condition variable (n = 4 articles), followed by the self-rated health, subjective health complaint, perception for benefit matter and limitation in daily activities variable, each of them are (n=2 articles). Further studies are needed to develop an appropriate instrument in assessing the factors of the needs of the elderly in full, namely the factors of the needs of the elderly which are seen from the clinical aspect of the utilization of health services at the Puskesmas and Posyandu.